PEMBUATAN KARBON AKTIF MONOLIT DARI KAYU KARET MENGGUNAKAN AKTIVATOR KOH DAN HNO3 UNTUK APLIKASI SUPERKAPASITOR - Zulkifli '; Erman Taer; Sugianto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Activated carbon monolith (ACM) was made from rubber wood for supercapacitor applications by using two activators, namely KOH and HNO3 . Carbonized sample were by N2 gas at a temperature of 600º C and were physically activated by CO2gas at 800º C for 2 hours. KOH solution of 1, 3 and 5M was used as chemical activation solution. ACM electrodes were tested in a two-electrode system, which was stainless steel as a current collector and a 1M H2SO4 solution as an electrolyte solution. Electrochemical characterization results by impedance spectroscopy methods showed an increase in the capacitive properties, followed by a decrease in cells resistance. The measurements obtained the best capacitance of 55.46 F/g. XRD patterns of the samples showed amorphous structure and SEM images showed that the addition of KOH solution resulted in the pore structure of macroporous and mesoporous combination. In conclusion, this current result showed that the activator of KOH and HNO3have improved the performance of the ACM rubber wood electrode.